Analysis of the Impact of Digital Transformation on Student Learning Outcomes in Islamic Education Subjects at MTsN 6 HSU - Muhammad Ikhsan; Syahrani (CV PUTRA PUBLISHER, 2025)
Digital transformation has become an integral aspect of progress in Islamic education, particularly in the teaching of Islamic Religious Education (PAI) at madrasas. This study aims to comprehensively describe the impact and significance of digital transformation in improving students' learning outcomes in PAI at MTsN 6 Hulu Sungai Utara, as well as to identify the supporting and inhibiting factors in its implementation. Employing a descriptive qualitative method with a case study design, the research collected data through field observation, in-depth interviews, and document analysis. The data were analyzed using Miles and Huberman's interactive model, encompassing data reduction, data presentation, and conclusion drawing. The findings indicate that digital transformation positively influences the effectiveness of PAI learning. Teachers have started to utilize digital platforms such as E-learning Madrasah, Google Classroom, and Qur'an Digital applications to enhance interaction and student participation. Learners demonstrated increased motivation and comprehension, although several challenges remain, including limited internet access, inadequate digital tools, and unequal digital literacy levels. The discussion highlights that the success of digital transformation largely depends on teachers' readiness as digital facilitators, institutional infrastructure support, and students' active engagement in using learning media. This transformation also drives a paradigm shift from conventional teaching methods toward more contextual, creative, and collaborative learning models. The study concludes that the implementation of digital technology in PAI learning at MTsN 6 Hulu Sungai Utara significantly contributes to improving both learning outcomes and educational interaction quality. Nevertheless, continuous professional development for teachers and institutional policy support are essential to ensure that digital transformation proceeds effectively and sustainably.